A BSDE with Delayed Generator Approach to Pricing under Counterparty Risk and Collateralization. (2nd August 2016) - Cordoni, Francesco; Di Persio, Luca
Abstract : We consider a nonlinear pricing problem that takes into account credit risk and funding issues. The aforementioned problem is formulated as a stochastic forward-backward system with delay, both in the forward and in the backward component, whose solution is characterized in terms of viscosity solution to a suitable type of path-dependent PDE .